Leitura em sala de aula: para além das páginas do livro didático - Queiroz , João Everton Leandro de (2023)
The research deals with reading in the classroom, with the aim of improving this language practice in students. To this end, we take a reading study chapter (chapter 1) from the textbook entitled ‘Singular e Plural: leitura, produção e estudos de linguagem’, authored by Marisa Balthasar and Shirley Goulart (2018), in order to support the purpose of the research, which aims to analyze the reading activities offered in the aforementioned book, considering the reading skills necessaries for students in the eighth year of Elementary School at a municipal public school in Sapé-PB. The proposal is justified by the need to improve the level of reading proficiency of students, with and without the use of complementary activities to textbooks, in an attempt to understand the question: What are the contributions of the reading proposals offered in the textbook ‘Singular e Plural: leitura, produção e estudos de linguagem’ to improve the reading proficiency of eighth-year elementary school students? To theorize the research, we take the works of Orlandi (1998), (2005), (2010); Brandão (2012), Coracini (1995), Rojo (2009), Koch and Elias (2014), Lajolo (2010), Zilberman (2009), Pinheiro (2008), (2018), Bajour (2012). This is action research, with a qualitative basis and an interventionist nature. Regarding the methodology, the study starts from a documentary analysis, which analyzes the textbook and applies an initial diagnostic activity, chapter 1 extracted; then, through reading workshops, the final activity developed, with pedagogical suggestions to assess the corpus analyzed from the perspective of French Discourse Analysis, through proposed activities. Regarding the results obtained in the research, it is clear that textbook brings relevant contributions to the teaching of Portuguese, especially by working on the social character of the language. These contributions were enhanced when adapted to the student's context.